求个题 x(1+y^2)-ln(x^2+2y)=0 求y'(0)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 07:24:17
求个题x(1+y^2)-ln(x^2+2y)=0求y''(0)求个题x(1+y^2)-ln(x^2+2y)=0求y''(0)求个题x(1+y^2)-ln(x^2+2y)=0求y''(0)x(1+y^2)-l
求个题 x(1+y^2)-ln(x^2+2y)=0 求y'(0)
求个题 x(1+y^2)-ln(x^2+2y)=0 求y'(0)
求个题 x(1+y^2)-ln(x^2+2y)=0 求y'(0)
x(1+y^2)-ln(x^2+2y)=0
因为y是关于x的方程
所以对x求导得:
1+y^2+2xy*y'-1/(x^2+2y)*(2x+2y')=0
把x=0代入x(1+y^2)-ln(x^2+2y)=0
可解得y(0)=1/2
再把x=0,y(0)=1/2代入1+y^2+2xy*y'-1/(x^2+2y)*(2x+2y')=0
则5/4-2y'(0)=0
所以y'(0)=5/8
x(1+y^2)-ln(x^2+2y)=0
对x求导:
(1+y^2)+x*2y*dy/dx
-(x^2+2y)^(-1)*(2x+2dy/dx)
(1+y^2)(x^2+2y)+(2xy(x^2+2y)-2x-2)dy/dx=0
dy/dx=
(2xy(x^2+2y)-2x-2)/[(1+y^2)(x^2+2y)]
x=0代入:x...
全部展开
x(1+y^2)-ln(x^2+2y)=0
对x求导:
(1+y^2)+x*2y*dy/dx
-(x^2+2y)^(-1)*(2x+2dy/dx)
(1+y^2)(x^2+2y)+(2xy(x^2+2y)-2x-2)dy/dx=0
dy/dx=
(2xy(x^2+2y)-2x-2)/[(1+y^2)(x^2+2y)]
x=0代入:x(1+y^2)-ln(x^2+2y)=0 y=1/2
x=0 y=1/2代入:
dy/dx=
(2xy(x^2+2y)-2x-2)/[(1+y^2)(x^2+2y)]
dy/dx=-5/8
收起
求导y=ln ln ln(x^2+1)
y≈ln(1-2x)-ln(1-x)求化简
y=ln(ln^2(ln^3 x))求导数
y=ln(2x^-1)求导
y=ln(1+x^2)求导
y=ln^2(1-x)求导
求导:y=[ln(1-x)]^2
已知ln(x-y)+ln(x+2y)=ln2+ln(x)+ln(y),求x/y的值.
y=ln(x+√x^2+1),求y
求个题 x(1+y^2)-ln(x^2+2y)=0 求y'(0)
求导y=ln(x+(4+x^2)^1/2)
y=ln(x+√(1+x^2))的导数
求导:y=ln(x+根号下(1+x^2))
y=ln(x+√1+X^2)的导数
求y=ln^x(2x+1)的导数
证明:y=x-ln(1+x^2) 单调递增
y=ln(x+√1+x^2)求导
y=ln√(x/1+x^2)如何求导?